Deciphering ‘Arab hospitality’: Identifying key characteristics and concerns - Stephenson, M. L. *; Nazia Ali, (Routledge, 2018)
There exists a symbolic and socio-cultural relationship between hospitality and Arab populations, which also has its origins in the three Abrahamic (monotheistic) faiths—Christianity, Islam and Judaism. This ‘Abrahamic legacy’ continues to be embedded in ‘Arab Hospitality’ but is being challenged by socio-political and economic transformations in the contemporary world. Deciphering Arab hospitality from the theology of Islam considers the many relations between the Arab host and the Arab, non-Arab and ‘othered’ guest, and the way in which this form of hospitality is associated with and guided by Islamic scripture. However, the chapter recognises that there are instances of authentic Arab hospitality rooted in the pre-Islamic era and embedded in Bedouin societies and cultures. The work further contextualises hospitality within the private and informal spheres of everyday life, particularly in relation to duties and obligations as well as conceptions of generosity. A subsequent discussion also recognises the role of Arab hospitality within commercial spaces, illustrating staged and commodified versions of hospitality, especially for tourists (non-Arabs) to consume. Such distancing of hospitality from its Abrahamic Bedouin legacy is further supported by an observation that some social spaces are being penetrated with inhospitable relations with the ‘other’ (non-Arab guest), thereby challenging pre-modern perceptions of Arab (or Bedouin) hospitality. The discussion finally indicates a concern that the rise of Islamophobia and its relationship to Arab communities further complicates and challenges socio-cultural-based notions of Arab communities as being hospitable and accommodating.